SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KELUARGA MISKIN MENGGUNAKAN LOGIKA FUZZY TSUKAMOTO - Ardi Mardiana; Dadan Zaliluddin; Desi Fitriani (INFOTECH journal, 2020)
The problem of poverty is one of the fundamental issues that become the center of government attention in any country. The goverment has sought to reduce poverty in every region. By launching various poverty alleviation programs, especially the family-based cluster support program 1, the goverment make activity programs to helping the poor families. In determine the poor families, so that not just anyone can receive the assistance provided by the government for poor families and the funds provided can be received by the people who really need. One of criteria will use in determine poor families from 14 poverty criteria by BPS version, broad building, income, and the comsumption of meat/egg. Test system created is a decision support system using fuzzy tsukamoto to help and increase performance from the selection process of who is entitled to get help from the government. This result, produce a decision support system and a list of poor families that deserve and do not deserve government assistance.